Form for reporting Iowa Christmas bird counts to Iowa Bird Life, John Carl Miller, December 17, 1988 - Miller, John Carlet al (1988)
Iowa Christmas bird counts of species found in Dubuque contributed by John Carl Miller, December 17, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed